Analysis and optimization of the selective crushing process based on high voltage pulse energy. (July 2022) - Zhao, Pengfei; Yang, Fan; Bai, Yuqi; Yan, Guanghui; Sun, Zongsheng; Zhao, Hongyu; Zhang, Bo
Highlights: Selectivity of HVP crushing on PV panels was evaluated. The change law of the selectivity of HVP crushing on PV panels was obtained. Mathematical correlation of operating parameters and selectivity was obtained. Significance order of the effect of operating parameters to selectivity was obtained. Best operating parameters of HVP crushing on PV panel was obtained. Abstract: With the development of photovoltaic (PV) energy, the recycling technology of end-of-life PV panels has received much attention; the existing recycling methods have various limitations. In this study, high-voltage pulse energy was used to crush PV panels, and the microscopic morphology, particle size structure, and elemental composition of the crushed products were analyzed. The liberation process and element enrichment during the high-voltage pulse crushing of PV panels were studied, the effect of each parameter on the selective crushing degree of high-voltage pulse crushing PV panels was obtained. Furthermore, a collaborative optimization study was carried out on the degree of selective crushing of various operating parameters. The significance order of the effect of various factors and the mathematical correlation between them were obtained. The best combination of operating parameters was obtained. The test results indicate that the source of high-efficiency liberation and element enrichment during the high-voltage pulse crushing of PV panels is the interface crushing and sequential selective crushing characteristics of high-voltage pulses. With the increase in electrode gap, the degree of selective crushing shows a increasing trend. As the voltage and pulses number increases, the degree of selective crushing first increases and then decreases. The significance of influence of each factor decreases in the following order: voltage > electrode gap > pulse number. When the operating conditions are 170 kV, 50 pulses, and 25 mm, the degree of selective crushing of product reached the maximum.